GE_GERICHTE P/18706/2017 vom 29. Januar 2018 - GE Cour de justice (2018)
ORDONNANCE PÉNALE ; OPPOSITION(PROCÉDURE) ; DÉFAUT(CONTUMACE) ; REPRÉSENTATION ; PROCURATION ; CITATION À COMPARAÎTRE | CPP.356.al4; CPP.127.al5; CPP.355.al2; LaCP.18